2006
DOI: 10.2214/ajr.04.1682
|View full text |Cite
|
Sign up to set email alerts
|

Combined Endorectal and Phased-Array MRI in the Prediction of Pelvic Lymph Node Metastasis in Prostate Cancer

Abstract: Incorporation of the Partin nomogram results and MRI findings regarding both extracapsular extension and seminal vesicle invasion improves the MR prediction of LNM in patients with prostate cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(49 citation statements)
references
References 36 publications
(62 reference statements)
3
42
0
4
Order By: Relevance
“…Limitations in the accuracy of existing tools confirm that there is a need for novel biomarkers and imaging tools that are associated with the biologic behavior of PCa to enhance the predictive accuracy of current tools. 33,49,50 Catalogue of Available Predictive Tools Predicting prostate cancer on initial biopsy Table 1 shows nomograms for predicting PCa on initial biopsy. Eastham et al developed the first nomogram for predicting PCa on initial biopsy in men who had a c-index of 0.75.…”
Section: Suboptimal Predictive Accuracymentioning
confidence: 99%
“…Limitations in the accuracy of existing tools confirm that there is a need for novel biomarkers and imaging tools that are associated with the biologic behavior of PCa to enhance the predictive accuracy of current tools. 33,49,50 Catalogue of Available Predictive Tools Predicting prostate cancer on initial biopsy Table 1 shows nomograms for predicting PCa on initial biopsy. Eastham et al developed the first nomogram for predicting PCa on initial biopsy in men who had a c-index of 0.75.…”
Section: Suboptimal Predictive Accuracymentioning
confidence: 99%
“…They found that the 1997 Partin tables's AUC for predicting LNI was 0.818-0.837, while the 2001 tables AUC was 0.807. Work was completed in an effort to compare the AUC of MRI findings alone to the 2001 Partin table nomogram, in patients undergoing standard pelvic lymph node dissection (pLND) after RP [101]. On multivariate analysis, significant predictors of LNI were MRI findings (p = 0.002), PSA (p = 0.004), greatest percent of cancer in all biopsy cores (p = 0.007) and GS (p = 0.007).…”
Section: • Ecementioning
confidence: 99%
“…The sensitivity of MRI for LNM may be increased through use of these compounds, since they appear to permit detection of metastases in normal-sized nodes [73,75] . A study of 411 consecutive patients [32] showed that MRI was an independent statistically significant predictor of LNM Wang L. MRI and management of prostate cancer (P = 0.002), with sensitivity and specificity of 27.27% and 98.46%, respectively, and positive predictive value and negative predictive value of 50% and 95.99%, respectively. On multivariate analysis, prediction of lymph node status using the model that included all MRI variables (ECE, SVI, and LNM) along with the Partin nomogram results had a significantly greater AUC than the univariate model that included only MRI LNM findings (AUC = 0.892 vs 0.633, respectively, P < 0.01).…”
Section: Detection Of Lnmmentioning
confidence: 99%
“…Moreover, the nomograms are limited because they do not incorporate the results of imaging studies that could guide interventions to control local disease. Thus, a technique that noninvasively demonstrates the presence, extent, and biologic potential of prostate cancer could contribute incremental value to clinical nomograms and variables and make a substantial contribution to the decision-making process for individualized treatment [32,33] . Magnetic resonance imaging (MRI) is a technique which makes safer, more individualized therapies possible due to high spatial resolution, superior contrast resolution, multiplanar capability ( Figure 1) [34][35][36][37][38] .…”
Section: Introductionmentioning
confidence: 99%